Precariousness and viability of small peasant production in the new millennium - de Luna López, Humberto (Cooperativismo & Desarrollo, 2021)
The objective of this article is to expose the processes of reconfiguration of peasant society, to face preca-riousness and perpetuate itself as a segment of the population that presses wages with a downward trend, by adding to the growth of population surpluses, in a province of the north-central Mexico called Zacatecas. In this place, 4 out of 10 Zacatecans live in rural áreas. Furthermore, in 2007 there were 124 861 small producers and by 2016 there were 255 236, mainly common landowners and community members who produce for their own consumption on temporary lands and without interference in market prices, for which a scenario of poverty has prevailed. The document was structured from a critical perspective and a hypothetical deductive methodology was used for its analysis. From the information available in research on small producers and official data, it was possible to understand the processes in which the activities of peasants take place in the world and, specifically, in Zacatecas. In this place, the peasant population lives in towns with less than 2500 inhabitants, which is why they are considered rural populations. The precariousness in which they develop has implied strengthening and improving their agricultural practices with the promotion of enterprises such as schools for rural women and young people, by accompanying producers promoted by the government apparatus with the support of the United Nations Organization for Food and Agriculture (FAO). The purpose was to strengthen the peasant socioeconomic unit as part of the underpinning for their subsistence reproduction, without moving to profitable and profitable production. Despite the economic and social adversities of uncertainty and preca-riousness, the peasants remain.
Keywords: precariousness; viability; small peasant production; Zacatecas